KEPENTINGAN KANADA MENYETUJUI PERJANJIAN INDONESIA-CANADA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (ICA-CEPA) - Amanda, Liranti; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze Canada’s interests in concluding the Indonesia-Canada Comprehensive Economic Partnership Agreement (ICA-CEPA). The agreement constitutes a pivotal component in achieving Canada’s Indo-Pacific Strategy, serving as a national framework to secure Canada’s position within the region. Furthermore, this research elucidates the rationale behind Canada’s selection of Indonesia as a key trading partner and examines the strategic benefits the ICA-CEPA provides for the country. The research findings indicate that Canada’s interest in entering the ICA-CEPA with Indonesia serves as a strategic step toward fulfilling its Indo-Pacific Strategy by positioning Indonesia as a primary trading partner in the region. Moreover, the agreement, which was finalized through ten rounds of negotiations, was officially signed in September 2025 and entered into force in 2026. Keywords: ICA-CEPA, Indo-Pacific, Cooperation, Agreement